BUILDING COMIC IMAGINATION THROUGH POLITICAL PARODY: A CRITICAL DISCOURSE ANALYSIS ON DONALD TRUMP IN THE PRESIDENT SHOW AND SATURDAY NIGHT LIVE’S THE PRESIDENTIAL DEBATE - Isna Ardyani Fataya (Universitas Gadjah Mada, 2020)
The number of Americans watching political comedy shows has significantly growing recent years. The views increase as TV channels spread their programs into social media, such as YouTube. The comic and funny aspects depicted in the political parody can be in the forms of imitation, impersonation, and reflection of one’s character, expression, and appearance. This paper aims to investigate American TV programs, The President Show and Saturday Night Live’s The Presidential Debate, by employing humor theory seen from Van Dijk’s critical discourse analysis. The dialogues used by the impersonators are analyzed to figure out the elements of funny features, comedy, and parody. Hence, the purpose of this study is to answer whether or not the discourse mechanism can build humor in The President Show and Saturday Night Live’s The Presidential Debate. The data apply ten Comedy Central’s YouTube videos and four Saturday Night Live’s YouTube videos. The data comprises of political and power discourse. The analysis concludes that both shows utilize some aggressive strategies to criticize Trump’s character, such as metaphor to represent policies, contrast to illustrate positive self-representation, and hyperbole to demonstrate racism. While Saturday Night Live applies Hillary Clinton to contrast Trump’s image. Saturday Night Live contrast Trump by applying strategies such as disclaimer, implication, incongruity, aggressive, and illustration to criticize his personalities and his controversial political decisions.